2018
DOI: 10.2478/hukin-2018-0022
|View full text |Cite
|
Sign up to set email alerts
|

Does Sodium Citrate Cause the Same Ergogenic Effect as Sodium Bicarbonate on Swimming Performance?

Abstract: The aim of this study was to investigate the effect of ingesting sodium bicarbonate (SB) and sodium citrate (SC) on 400 m high-intensity swimming performance and blood responses. Six nationally ranked male swimmers (20.7 ± 2.1 yrs; 184 ± 6 cm; 79.9 ± 3.9 kg; 10.6 ± 1% body fat) participated in a double blinded, placebo controlled crossover trial. Ninety minutes after consuming SB (0.3 g·kg-1), SC (0.3 g·kg-1) or a placebo (PL) participants completed a single 400-m freestyle maximal test on three consecutive da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 24 publications
6
15
0
Order By: Relevance
“…This effect is probably due to the presence of three negative charges in the molecule (while bicarbonate ions have only one) which dispose of H + and increase [HCO 3 − ] 57 . This evidence reinforces the hypothesis that timing and dosage of SC ingestion may represent key features to achieve significant functional improvement during exercise and their adequate combination probably lacks when a change in pH is not associated with an ergogenic effect 30,54,58‐63 . In fact, some initial results suggest that to supplement SC at the dose of 0.5 g × kg −1 bw or higher with a timing above 90 minutes is able to improve endurance performance(3 km and 5 km time trials in elite multidisciplinary athletes and well‐trained college runners respectively) in presence of controlled experimental conditions in double‐blind randomized trials 22,45 .…”
Section: Effects On Exercisesupporting
confidence: 59%
“…This effect is probably due to the presence of three negative charges in the molecule (while bicarbonate ions have only one) which dispose of H + and increase [HCO 3 − ] 57 . This evidence reinforces the hypothesis that timing and dosage of SC ingestion may represent key features to achieve significant functional improvement during exercise and their adequate combination probably lacks when a change in pH is not associated with an ergogenic effect 30,54,58‐63 . In fact, some initial results suggest that to supplement SC at the dose of 0.5 g × kg −1 bw or higher with a timing above 90 minutes is able to improve endurance performance(3 km and 5 km time trials in elite multidisciplinary athletes and well‐trained college runners respectively) in presence of controlled experimental conditions in double‐blind randomized trials 22,45 .…”
Section: Effects On Exercisesupporting
confidence: 59%
“…In the primary search, there was a total of 221 results; 204 results were excluded after reading the title or abstract (Figure 1). After reading 17 full-text papers, nine studies were found that satisfied the inclusion criteria (Campos et al, 2012;de Salles Painelli et al, 2013;Joyce et al, 2012;Kumstát et al, 2018;Lindh et al, 2008;Mero et al, 2013;Pierce et al, 1992;Pruscino et al, 2008;Yong et al, 2018). There was an additional 818 search results in the secondary search, but there were no additional studies that met the inclusion criteria.…”
Section: Search Resultsmentioning
confidence: 99%
“…L -1 . In four of these studies, the SMD was towards the "favors sodium bicarbonate" side of the forest plot, and the 95% CIs of these studies overlapped (Joyce et al, 2012;Kumstát et al, 2018;Lindh et al, 2008;Pruscino et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typical alkaline buffers can attenuate extracellular acidosis by acting as a physical and chemical buffer 18,19,20 . Pyruvate, on the other hand, can be transferred into cells as an intracellular buffer to attenuate metabolic acidosis 21 .…”
Section: Introductionmentioning
confidence: 99%